2019
DOI: 10.1002/joc.6158
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impact of Pacific Decadal Oscillation on autumn droughts in North China based on the Palmer drought severity index

Abstract: This study assesses the impact of the Pacific Decadal Oscillation (PDO) on the severity of autumn droughts in North China (ADNC) during the period of 1962–2013. The ADNC are defined using the Palmer drought severity index (PDSI). The results show that the ADNC are more severe during negative PDO phases than during positive PDO phases. During the negative PDO phase, both the autumn precipitation and the Penman–Monteith reference evaporation (PET_pm) play roles in the significant severity of the ADNC. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, given the short observational record, the complexity of multivariate physical and ecological variability, and the inability to satisfactorily model these complex interactions, mechanistic understanding of ecological correlations with climate indices remains poor. As a result, the PDO and NPGO indices are commonly employed as covariates in correlative studies that fit statistical models to estimate the effects of climate variability for fisheries management (25,27,28), hydrology (29)(30)(31), agriculture (32)(33)(34), and economic planning (35,36). Statistical approaches commonly used in these correlative studies may produce era-dependent errors in inference when confronted with nonstationary relationships of the kind we document here (14,26,37,38).…”
Section: Resultsmentioning
confidence: 99%
“…However, given the short observational record, the complexity of multivariate physical and ecological variability, and the inability to satisfactorily model these complex interactions, mechanistic understanding of ecological correlations with climate indices remains poor. As a result, the PDO and NPGO indices are commonly employed as covariates in correlative studies that fit statistical models to estimate the effects of climate variability for fisheries management (25,27,28), hydrology (29)(30)(31), agriculture (32)(33)(34), and economic planning (35,36). Statistical approaches commonly used in these correlative studies may produce era-dependent errors in inference when confronted with nonstationary relationships of the kind we document here (14,26,37,38).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, either heat events or drought events in China has been increased since the late 1990s, possibly due to the combined effects of long term trend of global warming and multi-decadal/multi-annual variability (e.g. Pacific Decadal Oscillation, Atlantic Multidecadal Oscillation, and El Nino) 42 , 43 , 45 . As a result, CDHEs have increased spatially and temporally.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, CDHEs are found to have become more persistent. As CDHE is a concurrent event of drought and heat, some studies have already found that both heat and drought events in China have been prolonged during the past decade 43 , 46 mainly because of global warming, the influence of ocean conditions, and regional land-use and land management changes. Noticeably, there may exist positive feedback between heat events and drought events 47 , 48 , especially under the global warming background.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To detect meteorological drought as well as flood, various indexes are proposed, such as the Palmer Drought Index (PDSI) [18] and the Standardized Precipitation Index (SPI) [19], which have been widely used all over the world [20,21]. PDSI, which is based on the anomalies of the supply and demand components in the water balance equation, has a complex structure with an exceptionally long memory [22,23].…”
Section: Introductionmentioning
confidence: 99%